Bacteriobiota and Chemical Changes during the Ripening of Traditional Fermented “Pirot ‘Ironed’ Sausage” - Svetlana Bogdanović; Slaviša Stanković; Tanja Berić; Igor Tomasevic; Volker Heinz; Nino Terjung; Ivica Dimkić (Foods, 2023)
“Pirot ‘ironed’ sausage“ (Pis) is a traditional, fermented sausage, made from different types of meat (beef and chevon), without additives or starter cultures. The physical–chemical properties (pH, water activity, fats, moisture, and protein contents) were examined in the initial meat batter stuffing and during ripening. Total bacterial diversity was examined at different time points using both culturable (traditional) and non-culturable (NGS sequencing) approaches. During the ripening, a decrease in pH value, aw, and moisture content was observed, as well as an increase in protein and fat content. At least a two-fold significant decrease was noted for colorimetric values during the ripening period. The dominance of Proteobacteria and Firmicutes was observed in the non-culturable approach in all studied samples. During the ripening process, an increase in Firmicutes (from 33.5% to 63.5%) with a decrease in Proteobacteria (from 65.4% to 22.3%) was observed. The bacterial genera that were dominant throughout the ripening process were Lactobacillus, Photobacterium, Leuconostoc, Weissella, and Lactococcus, while Carnobacterium, Brochothrix, and Acinetobacter were found also, but in negligible abundance. Among the culturable bacteria, Latilactobacillus sakei (Lactobacillus sakei) and Leuconostoc mesenteoides were present in all stages of ripening.